2022
DOI: 10.1128/spectrum.00695-22
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Nitrate Dissimilation to Nitrate Consumption in narG - and napA -Containing Nitrate Reducers with Various Oxygen and Nitrate Supplies

Abstract: Nitrate reducers containing narG or napA are ubiquitous, but little is known about their functional performance in various environments. Our study provides an important clue that the nitrate consumption of narG -containing strains is mainly caused by dissimilatory reduction in the environments, while that of napA -containing nitrate reducers under anaerobic conditions is ascribed to nitrate dissimilation but under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 48 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Genes involved in nitrate import and reduction were present in MAG 30 (Table S1 ). Recent studies have revealed the role of napA in dissimilatory nitrate reduction under anaerobic conditions indicating that MAG 30 may perform dissimilatory reduction of nitrate to nitrite (Alcántara‐Hernández et al, 2009 ; Chen et al, 2022 ). Moreover, the presence of nir genes indicates the denitrifying capabilities of this Sumerlaeota MAG.…”
Section: Resultsmentioning
confidence: 99%
“…Genes involved in nitrate import and reduction were present in MAG 30 (Table S1 ). Recent studies have revealed the role of napA in dissimilatory nitrate reduction under anaerobic conditions indicating that MAG 30 may perform dissimilatory reduction of nitrate to nitrite (Alcántara‐Hernández et al, 2009 ; Chen et al, 2022 ). Moreover, the presence of nir genes indicates the denitrifying capabilities of this Sumerlaeota MAG.…”
Section: Resultsmentioning
confidence: 99%
“…Desert soils can support denitrifier communities (11,(30)(31)(32), and wetting soils following experimental drought can stimulate denitrification (19,20). Because we did not detect napA transcripts, it is possible that narG denitrifiers are better suited to remain active in hot and dry environments (33)(34)(35) to take advantage of resources flushed during brief anoxic periods after wetting (36)(37)(38)(39)(40)(41). While detecting narG transcripts does not conclusively demonstrate that biological processes were reducing NO 3…”
mentioning
confidence: 99%